2007
DOI: 10.1080/13921657.2007.10512814
|View full text |Cite
|
Sign up to set email alerts
|

ON THE SKULL MORPHOLOGY OF RACCOON DOG (NYCTEREUTES PROCYONOIDES) AND RED FOX (VULPES VULPES)

Abstract: Abstract. The aim of this work was to perform analysis of the skull morphology of red fox and raccoon dog and to examine their frontal sinuses (sinus frontalis) with the help of the methods of comparative anatomy and computed tomography. A total of 71 skulls of adult animals were used, 38 of red fox (22 male and 16 female) and 33 of raccoon dogs (21 male and 12 female). The most distinct morphological features were found in cranium bones, especially in frontal and occipital bones. The mandible was found to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…It has been shown that the frontal sinus of the Japanese wolf (Endo et al, 1997) is divided into small divisions by osseous partitions. In this respect, Jurgelėnas et al (2007) reported that the frontal sinus of red fox is divided by a very thin osseous partition while that of raccoon dog is divided by two well-defined osseous partitions. The latter authors added that the frontal sinus of red fox does not extend into the zygomatic process of frontal bone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that the frontal sinus of the Japanese wolf (Endo et al, 1997) is divided into small divisions by osseous partitions. In this respect, Jurgelėnas et al (2007) reported that the frontal sinus of red fox is divided by a very thin osseous partition while that of raccoon dog is divided by two well-defined osseous partitions. The latter authors added that the frontal sinus of red fox does not extend into the zygomatic process of frontal bone.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the anatomy and communications of the paranasal sinuses, three additional heads were macerated. The frontal sinus was exposed after removal of the osseous plate of the frontal bone (Jurgelėnas et al., 2007). To expose the maxillary recess, resection of the zygomatic arch was done followed by removal of the osseous plate at the junction of the lacrimal, zygomatic and maxillary bones.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifi cally, we observed a more developed external sagittal crest, wider more arched foramen magnum, deeper and wider masseteric fossa, and better developed mandibular notch and angular process in red foxes than in corsac foxes. Jurgelenas et al (2007) and Frackowiak et al (2013) found similar patterns in their comparison of the skulls of the red fox, raccoon dog (Nyctereutes procyonoides; Hidaka et al 1998) and arctic fox. Our study showed diff erences in the almost all measurements of both species particularly length of the molar row of maxilla and mandible.…”
Section: Discussionmentioning
confidence: 70%
“…Literature on comparative skull morphology of raccoon dogs is limited. Measurements of 71 skull, 38 of red fox and 33 of raccoon dogs, were analys ed for skull morphology and their frontal sinuses (sinus frontalis) using comparative anatomy and computed tomography by Jurgelėnas et al (2007). Jurgelėnas et al (2011) studied skulls of raccoon dogs and red foxes based on determination of differences in the skull shape between sexes and species and did not find differences between form of skull of female and male raccoon dogs and red foxes.…”
Section: Introductionmentioning
confidence: 99%